CoSe nanoparticles in-situ grown in 3D honeycomb carbon for high-performance lithium storage - Zhang, Tengsheng (2023)
Although transition metal selenides are considered to be extremely promising anode materials for lithium-ion batteries (LIBs), severe volume changes and low electronic conductivity are their huge and unavoidable challenges. To solve these problems, CoSe nanoparticles in-situ grown on the inner surface of every macropore of 3D honeycomb C is successfully synthesized by three simple steps: dense assembling of polystyrene spheres, calcination and gaseous selenylation. The sizes of CoSe and honeycomb pores are 10-15 nm and 190 nm, respectively. The content of CoSe is 72 wt%. This unique architecture guarantees high electrochemical activity, rapid reaction kinetics and excellent structural stability of CoSe, as identified by cycling and rate performance measurements, various electrochemical kinetics analyses and ex-situ characterization of the cycled electrode material. As a result, the CoSe@honeycomb C anode exhibits extraordinary cycling performance (823.5 mAh g-1 after 200 cycles at 0.5 A g-1, 610.1 mAh g-1 after 250 cycles at 2 A g-1, 247 mAh g-1 after 1500 cycles at 5 A g-1) and exceptional rate capability (261.9 mAh g-1 at 10 A g-1, 1491.4 mAh g-1 at 0.1 A g-1), demonstrating that it is a potential anode material for high-performance LIBs.